Formulation Of Conservation Guidelines For Residential Heritage Buildings In The Old City Of Ghadames, Libya - Ahsairat, Amal S.F (2013)
Libya is a treasure chest of heritage and ancient cultures. The old city of Ghadames (OCG), a UNESCO registered world heritage site, is an outstanding example of sound engineering practices providing comfort, functionality and cost-effectiveness in a uniquely Ghadamsi architectural style and traditional construction techniques. However, the level of understanding of the heritage buildings in Libya still remains very low and many heritage buildings are at risk from defects which in turn affects the Outstanding Universal Value (OUV) of the OCG. Furthermore, there is a significant lack of researches conducted on heritage buildings in Libya in general and in the OCG in particular. This research aims to determine the structural integrity of the residential heritage buildings of the OCG as well as to provide and develop conservation guidelines for repairing and conserving those heritage buildings. The methodologies used in this research include a literature review, analysis of case studies, and a survey of construction and defects of the residential heritage buildings of the OCG that has been conducted to generate sufficient data. Moreover, some information about issues and problems of conservation of the residential heritage buildings of the OCG are gathered by carrying out interviews with local experts on construction practices and two local official government departments in Libya which are, Ministry of Tourism and Municipality. The research concludes some conservation guidelines for the residential heritage buildings in the OCG; the most important of them were: the historic character of a property, distinctive features and construction techniques shall be retained and preserved. Deteriorated historic features shall be repaired rather than replaced. If the severity of deterioration requires replacement of a distinctive feature, the new feature shall match the old in design, colour, texture and materials. In addition, chemical treatments that cause damage to historic materials shall not be used. The research also finds that the lack of routine maintenance and severe environmental conditions have caused extensive damages to many OCG residential heritage buildings. The research's findings may be used to identify new or strengthened legal elements that Libya should take into account in its protected heritage area legal frameworks as well as to enhance conservation policies and the OUV of the OCG.